Which Agroforestry Practice Is Beneficial? A Comparative Assessment of the Traditional and the Improved Agroforestry Techniques in the Midhills of Nepal. (24th June 2021) - Paudel, Deepa; Tiwari, Krishna Raj; Raut, Nani; Sitaula, Bishal K.; Bhattarai, Suman; Timilsina, Yajna Prasad; Thapa, Shivaraj
Abstract : Farmers are predominantly adopting two forms of agroforestry, traditional and improved practices, in the midhills of Nepal, but their efficacy on a comparative basis is poorly assessed, so farmers often confuse whether to continue the traditional practice or embrace the improved practice. We carried out a study in six villages of three districts, interviewed 210 farmers adopting each practice, organized six focus group discussions, and interacted with 24 key informants to compare agroforestry practices from income generation and forest conservation perspectives. An individual household adopting the improved practice annually generated 841.60 US, which was more than two folds of the traditional practitioner. Similarly, the improved practitioner annually fulfilled 84% demand for forest products from the adopted agroforestry practice, whereas the traditional practitioner only fulfilled about 50%. The fodder, fuelwood, and timber productions were found to be significantly higher in the improved practice, whereas leaf litter production was found to be almost similar. The improved practitioners seemed to be self-sustained in forest products, where the traditional practitioners only satisfied half of their requirements from the agroforestry practice. The study concludes that the improved agroforestry practice is more beneficial compared to the traditional practice. Therefore, we suggest the traditional practitioners to modify their ongoing practice to enhance the contribution of agroforestry practice at the local level.